Cost‐effectiveness analysis of a model of first‐trimester prediction and prevention of preterm pre‐eclampsia compared with usual care. (19th October 2021) - Park, F.; Deeming, S.; Bennett, N.; Hyett, J.
ABSTRACT: Objectives: Pre‐eclampsia (PE) causes substantial maternal and neonatal mortality and morbidity. In addition to the personal impact on women, children and their families, PE has a significant economic impact on our society. Recent research suggests that a first‐trimester multivariate model is highly predictive of preterm (< 37 weeks' gestation) PE and can be combined successfully with targeted prophylaxis (low‐dose aspirin), resulting in an 80% reduction in prevalence of disease. The aim of this study was to examine the potential health outcomes and cost implications following introduction of first‐trimester prediction and prevention of preterm PE within a public healthcare setting, compared with usual care, and to conduct a cost‐effectiveness analysis to inform health‐service decisions regarding implementation of such a program. Methods: A decision‐analytic model was used to compare usual care with the proposed first‐trimester screening intervention within the obstetric population ( n = 6822) attending two public hospitals within a metropolitan district health service in New South Wales, Australia, between January 2015 and December 2016. The model, applied from early pregnancy, included exposure to a variety of healthcare professionals and addressed type of risk assessment (usual care or first‐trimester screening) and use of (compliance with) low‐dose aspirin prescribed prophylactically for prevention of PE. All pathways culminated in six possible health outcomes, ranging from no PE to maternal death. Results were presented as the number of cases of PE gained/avoided and the incremental increase/decrease in economic costs arising from the intervention compared with usual care. Significant assumptions were tested in sensitivity/uncertainty analyses. Results: The intervention produced, across all gestational ages, 31 fewer cases of PE and reduced aggregate economic health‐service costs by 1 431 186 Australian dollars over the 2‐year period. None of the tested iterations of uncertainty analyses reported additional cases of PE or higher economic costs. The new intervention based on first‐trimester screening dominated usual care. Conclusion: This cost‐effectiveness analysis demonstrated a reduction in prevalence of preterm PE and substantial cost savings associated with a population‐based program of first‐trimester prediction and prevention of PE, and supports implementation of such a policy. © 2020 International Society of Ultrasound in Obstetrics and Gynecology Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Análisis de la relación costo‐eficacia de un modelo de predicción y prevención de la preeclampsia pretérmino en el primer trimestre en comparación con la atención habitual Objetivos: La preeclampsia (PE) causa una importante mortalidad y morbilidad materna y neonatal. Además del impacto personal en las mujeres, los niños y sus familias, la PE tiene un importante impacto económico en nuestra sociedad. Las investigaciones recientes sugieren que un modelo multivariante del primer trimestre es altamente predictivo de la PE pretérmino (<37 semanas de gestación) y que puede combinarse con éxito con la profilaxis específica (aspirina a dosis bajas), lo que resulta en una reducción del 80% de la prevalencia de la enfermedad. El objetivo de este estudio fue examinar los posibles resultados para la salud y las implicaciones en cuanto a costos tras la introducción de la predicción y prevención de la PE pretérmino en el primer trimestre en un entorno de sanidad pública, en comparación con la atención habitual, y realizar un análisis de la relación costo‐eficacia para informar las decisiones de los servicios sanitarios respecto a la implementación de dicho programa. Métodos: Se utilizó un modelo de análisis de decisiones para comparar la atención habitual con la intervención propuesta de cribado en el primer trimestre dentro de la población obstétrica (n=6822) que acudió a dos hospitales públicos del servicio de salud de un distrito metropolitano en Nueva Gales del Sur (Australia) entre enero de 2015 y diciembre de 2016. El modelo, aplicado desde el comienzo del embarazo, contempló la exposición a una variedad de profesionales sanitarios y abordó el tipo de evaluación del riesgo (atención habitual o cribado en el primer trimestre) y el uso (cumplimiento) de la aspirina a dosis bajas prescrita de forma profiláctica para la prevención de la PE. Todas las vías culminaron en seis posibles resultados de salud, que iban desde la ausencia de PE hasta la muerte de la madre. Los resultados se presentaron como el número de casos de PE sucedidos/evitados y el aumento/disminución incremental de los costos económicos derivados de la intervención en comparación con la atención habitual. Los supuestos significativos se probaron mediante análisis de insensibilidad e incertidumbre. Resultados: La intervención produjo, para todas las edades gestacionales, 31 casos menos de PE y redujo los costes económicos agregados de los servicios sanitarios en 1.431.186 dólares australianos durante el periodo de 2 años. Ninguna de las iteraciones que se probaron de los análisis de incertidumbre reportaron casos adicionales de PE o mayores costos económicos. La nueva intervención basada en el cribado del primer trimestre prevaleció sobre la atención habitual. Conclusión: Este análisis de la relación costo‐eficacia demostró una reducción de la prevalencia de la PE pretérmino y un ahorro sustancial de costos asociados a un programa de predicción y prevención de la PE en el primer trimestre basado en la población, y apoya la implementación de dicha política. © 2020 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 与常规护理相比较，对一种早产先兆子痫的早期妊娠预测与预防模型的成本效率分析 目的: 先兆子痫(PE)造成大量产妇与新生儿的死亡率与发病率。除了对妇女、儿童及其家庭的个人影响之外，PE还对我们的社会产生重大的经济影响。近期研究表明，一个早期妊娠的多变量模型可高度预测早产PE(小于孕37周)并能与定向预防治疗(低剂量阿司匹林)成功结合，将患病率减少80%。本研究目的在于调查与常规护理相比，在公共医疗机构内引入对早产PE的早期妊娠预测和预防之后可能的健康预后及成本影响，并进行一次成本效率分析，使公共医疗卫生服务在对实施此项目做决策时了解情况。 方法: 采用一个决策分析模型在产科群体内(n=6822)将提议的早期妊娠筛检干预与常规护理做对比，该群体于2015年1月至2016年12月在澳大利亚新南威尔士州本地区健康服务内的两家公立医院接受产检。从妊娠早期开始应用该模型，包括暴露于各种各样的医疗保健专业人员并处理风险评估类型(早期妊娠筛检常规护理)和服用(依从)医生开的预防性低剂量阿司匹林来预防PE。所有路径最终有六种可能的健康结局，从无PE到产妇死亡。研究结果以PE病例数的增加/避免，与常规护理相比因干预而引起的经济成本的递增/递减为依据。对主要假设用低灵敏度/不确定性分析进行测试。 结果: 在所有胎龄中，干预在两年期间将PE减少了31例并将经济卫生服务合计成本减少了1, 431, 186澳元。不确定性分析的检测迭代未报告额外的PE病例或更高的经济成本。基于早期妊娠筛检的新干预优于常规护理。 结论: 成本效率分析证明了早产PE患病率减少和大量成本节约是与基于人群的PE早期妊娠预测与预防项目相联系的，并支持此种政策的实施。© 2020年国际妇产科超声学会。